Ni de aquí ni de allá: the Dreamers’ Audiovisual Self-Narration and Representation - Anna Marta Marini (Cinergie, 2019)
In recent years, the US immigration system has shown increasing signs of failure, as it seems unable to cope with the flows of immigration nor the consolidated existence of undocumented immigrants in the country. In spite of the intense ongoing public debate on the topic, the immigrants’ perspective is often absent; the immigrant community itself—whether documented or not—is often rendered invisible and voiceless in the public sphere. Consequently, grassroot immigrant activism movements have emerged and with them a diverse production of audiovisual products related to immigrant justice. Among the most active organizations, those related to undocumented youth certainly stand out; in particular, it’s prominent the engagement of the Dreamers, recipients or potential recipients of the DACA (Deferred Action for Childhood Arrivals) program established in 2012. Documentaries and activist videos related to immigrant justice are chiefly participatory and rely on storytelling, exploiting the effectiveness of personal experiences in stimulating interest, awareness and compassion in the public. Young undocumented people admit to their controversial status using video as a mean of expression, resistance and freedom, voicing their commitment and struggle to fit in the American society, their fear of deportation and the downsides intrinsic to the DACA opportunity.